2020
DOI: 10.1016/j.immuni.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded Protein Response Mediator PERK Governs Myeloid Cell-Driven Immunosuppression in Tumors through Inhibition of STING Signaling

Abstract: The primary mechanisms supporting immunoregulatory polarization of myeloid cells upon infiltration into tumors remain largely unexplored. Elucidation of these signals could enable better strategies to restore protective anti-tumor immunity. Here, we investigated the role of the intrinsic activation of the PKR-like endoplasmic reticulum (ER) kinase (PERK) in the immunoinhibitory actions of tumorassociated myeloid-derived suppressor cells (tumor-MDSCs). PERK signaling increased in tumor-MDSCs, and its deletion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 63 publications
4
106
1
Order By: Relevance
“…PERK ablation led to a reprogramming of MDSC functionality, specifically, to initiate a type I interferon anti-tumor response. More importantly, similar anti-tumor effects can be achieved with the exogenous administration of PERK inhibitors ( 166 ).…”
Section: Methods To Prevent Myeloid Cell Contribution To Cancer Growtmentioning
confidence: 99%
See 1 more Smart Citation
“…PERK ablation led to a reprogramming of MDSC functionality, specifically, to initiate a type I interferon anti-tumor response. More importantly, similar anti-tumor effects can be achieved with the exogenous administration of PERK inhibitors ( 166 ).…”
Section: Methods To Prevent Myeloid Cell Contribution To Cancer Growtmentioning
confidence: 99%
“…Recent studies have attempted to explain why tumor-associated immunosuppressive myeloid cells cannot simply be binned in an M1/M2-like dichotomy, and Mohamed et al ( 166 ) describe ER stress as a potential mechanism. Undefined tumoral signaling causes an upregulation in the unfolded protein response of MDSCs, leading to an activation of the intermediate media PERK and NRF2 drive the immunoregulatory phenotype.…”
Section: Methods To Prevent Myeloid Cell Contribution To Cancer Growtmentioning
confidence: 99%
“…ER stress induced the expression of TNF-related apoptosis-induced ligand receptors (DR5) and lectin-type oxidized LDL receptor 1 (LOX1) and the conversion of neutrophils to polymorphonuclear MDSCs. The reduced NRF2 signalling favoured the accumulation of cytosolic mitochondrial DNA and consequent expression of antitumour type I interferon, in a STING-dependent manner 97 . …”
Section: Metabolic Characteristics Of Mdscsmentioning
confidence: 99%
“…The deletion of PERK or treatment with the selective inhibitor of PERK AMG-44 reduces Nrf2 transcription, resulting in ROS overexpression, causing mitochondrial damage, impeding the immunosuppression of MDSCs, and increasing the infiltration of CD8 + T cells. This situation can be antagonized by the addition of the Nrf2 inducer sulforaphane [98]. According to the above report, it can be concluded that Nrf2overexpression and deletion affect the immunoinhibitory activity of MDSCs.…”
Section: Inhibition Of Immunosuppressive Functionsmentioning
confidence: 91%
“…Treatment with Nrf2-inducing triterpenoids, such as omaveloxolone (RTA-408), CDDO-Me (RTA-402), and CDDO-Im (RTA-403), increases the transcriptional activity of Nrf2, which attenuates the production of ROS, abrogates the immune suppressive effect of MDSCs, and protects immune cells and tissues from oxidative stress [95][96][97]. However, a recent study has demonstrated that Nrf2 is activated by PKR-like endoplasmic reticulum (ER) kinase (PERK) in tumor-infiltrating MDSCs, giving MDSCs the potential for immunosuppression [98]. The deletion of PERK or treatment with the selective inhibitor of PERK AMG-44 reduces Nrf2 transcription, resulting in ROS overexpression, causing mitochondrial damage, impeding the immunosuppression of MDSCs, and increasing the infiltration of CD8 + T cells.…”
Section: Inhibition Of Immunosuppressive Functionsmentioning
confidence: 99%